Implementasi Nilai-Nilai Persatuan Dan Kemanusiaan Dalam Tradisi Sambatan Di Desa Karangan Kecamatan Jumantono Kabupaten Karanganyar (Studi Kasus di Desa Karangan Kecamatan Jumantono) - Kartikasari, Kengkin Dita Hesti; , Drs, YULIANTO BAMBANG SETYADI, M.Si (2016)
This study aims to describe the implementation, the constraints and the efforts in the implementation of the values of unity and humanity in the tradition of a splice in the village of Karangan Jumantono district of Karanganyar regency. Collecting data in this study with interviews, observations, and documents. Data analysis techniques by applying interactive models through data collection, reduction, presentation, and drawing conclusions. Test the validity of the data in this study by means of triangulation techniques and resources. The results showed that: 1) Implementation of the values of unity in the tradition of a splice village in the village of Karangan District of Jumantono Karanganyar Regency which reflected the same feeling in togetherness and kinship between the people, compelled by the nature of human nature as a creature of social, existence of a needs dependency between human one with others, the encouragement of the same soul and the same height low and their urge to help the distress of others. 2) Implementation human values in the tradition of a splice in the village of Karangan District of Jumantono Karanganyar Regency value contained strong unity in the tradition a splice that despite coming from a wealthy family, the poor, and the different levels of education and work to make the spirit of unity becomes stronger. A splice is a form of cooperation are joined together in helping meringan-the work of community members. 3) Obstacles in implementing values of unity and humanity in the tradition of a splice in the village of Karangan District of Jumantono Karanganyar Regency is jealous and envious as well as residents who migrated; 4) The work done by the community to overcome the barriers to the implementation of the values of unity and humanity in the tradition of a splice in the village of Karangan District of Jumantono Karanganyar Regency namely counseling and study that followed about the material importance of giving help to others who really need assistance or help.